2016
DOI: 10.1111/comt.12099
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Biographies of Media: On the Role of Narratives, Anecdotes, and Storytelling in the Construction of New Media's Histories

Abstract: The article proposes the notion of "biographies of media" to address the complex ways through which media change is the subject of narration and storytelling. This concept provides theoretical tools to unveil how different narratives contribute to shape media's identities and to carry particular representations of their roles in our society and everyday life. Relying on theoretical approaches to storytelling and to the biographical genre, as well as on a range of examples from media history, the article shows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 54 publications
(34 reference statements)
0
32
0
Order By: Relevance
“…At this early stage, the Internet did not need a history; rather it needed what the media historian Simone Natale calls a 'biography' (Natale 2016a), a story about the life of the medium to be recounted starting from a mythical genesis. 4 It is not by chance that the first books on Internet history were written with the very same enthusiasm that digital technologies were exciting in Western societies: successful works such as Where Wizards Stay up Late: The Origins of the Internet (Hafner and Lyon 1996) and Casting the Net: From ARPANET to Internet and Beyond (Salus 1995) are two examples of how the literature celebrated the glorious lives of Internet pioneers.…”
Section: The Dominant Narrative Of Internet Historymentioning
confidence: 99%
See 1 more Smart Citation
“…At this early stage, the Internet did not need a history; rather it needed what the media historian Simone Natale calls a 'biography' (Natale 2016a), a story about the life of the medium to be recounted starting from a mythical genesis. 4 It is not by chance that the first books on Internet history were written with the very same enthusiasm that digital technologies were exciting in Western societies: successful works such as Where Wizards Stay up Late: The Origins of the Internet (Hafner and Lyon 1996) and Casting the Net: From ARPANET to Internet and Beyond (Salus 1995) are two examples of how the literature celebrated the glorious lives of Internet pioneers.…”
Section: The Dominant Narrative Of Internet Historymentioning
confidence: 99%
“…Similarly, the radio drama The War of the Worlds, narrated by Orson Wells on CBS in 1938, is still used to describe the power of radio and the capacity of broadcasting to terrorize and drive the audience to specific behaviours. Even if historians and social scientists have demonstrated that there is no proof of the train effect, and that the War of Worlds terrorized only a small part of its audience, such anecdotes persist as foundational narratives of the birth of these media (Natale 2016a).…”
Section: The Narratives Of the Internet's Originsmentioning
confidence: 99%
“…My own use of the term, however, aims to stress the narrative character of biographical recounting. In this regard, biographies of media can be defined as the bodies of narratives unfolding and representing the lifespans of different media (Natale, 2016).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Such problems are also connected to the particular narratives through which the process of technological change is represented and understood (Natale, forthcoming). As Edgerton () effectively underlines, we tend to give emphasis to the moment of first design of a technology, failing to grasp that technologies continue to change after they are introduced, and that the history of innovation does not concern just “new” media.…”
Section: Searching For Old Mediamentioning
confidence: 99%
“…“Old media” have acquired such a strong and stable position in our imagination that they contribute to defining how media enter into the public sphere, the everyday life, as well as the inner life of perceptions and feelings. Media, after all, are not only “things”; they are also cultural constructions that shape our everyday experience, and provide us with meanings and narratives to make sense of the transformations and changes experienced throughout life (Natale, forthcoming; Natale & Balbi, ).…”
Section: Conclusion: Imagining Old Mediamentioning
confidence: 99%